Fibroblast growth factor receptor 3 in hepatocytes protects from toxin-induced liver injury and fibrosis - Abbie E. Fearon; Coenraad F. Slabber; Andrii Kuklin; Marc Bachofner; Luigi Tortola; Lea Pohlmeier; Sophia Pantasis; Thorsten Hornemann; Lin Chen; Manfred Kopf; Sabine Werner (iScience, 2021)
Summary: The liver's remarkable regenerative capacity is orchestrated by several growth factors and cytokines. Fibroblast growth factor receptor 3 (Fgfr3) is frequently overexpressed in hepatocellular carcinoma and promotes cancer aggressiveness, whereas its role in liver homeostasis, repair and regeneration is unknown. We show here that Fgfr3 is expressed by hepatocytes in the healthy liver. Its major ligand, Fgf9, is mainly expressed by non-parenchymal cells and upregulated upon injury. Mice lacking Fgfr3 in hepatocytes exhibit increased tissue necrosis after acute toxin treatment and more excessive fibrosis after long-term injury. This was not a consequence of immunological alterations in the non-injured liver as revealed by comprehensive flow cytometry analysis. Rather, loss of Fgfr3 altered the expression of metabolic and pro-fibrotic genes in hepatocytes. These results identify a paracrine Fgf9-Fgfr3 signaling pathway that protects from toxin-induced cell death and the resulting liver fibrosis and suggests a potential use of FGFR3 ligands for therapeutic purposes.